Suggestion on tax policy for promoting the PPP projects of charging infrastructure in China. (10th February 2018) - Yang, Tong; Long, Ruyin; Li, Wenbo
Abstract: Tax is an exogenous variable of the vehicle charging infrastructure in a Public–Private Partnership (PPP), and tax policy will play a great role in regulation during the contract cooperation in PPP mode for vehicle charging infrastructure. This study analyzed the relevant tax policy of China's current vehicle charging infrastructure PPP projects, and identified several problems, such as a low level of legislation, lack of fairness, many ambiguous areas, lack of refinement, obsolete tax incentives, lack of pertinence, low degree of policy coordination and poor systematization. To perfect the tax policy of a vehicle charging infrastructure PPP project, it is necessary to give policy suggestions based on the establishment of rules and regulations, classification of tax-related expenditure, construction of differentiated dynamic tax preferential policies and construction of a multi-level coordination and supporting policy system. Project experience should also be summarized, to create a favorable tax policy environment for the forecasted rapid development of vehicle charging infrastructures. Highlights: Tax is an exogenous variable of the vehicle charging infrastructure in a PPP project. Analyzed the relevant tax policy of China's vehicle charging infrastructure PPP projects. To create a favorable tax policy environment for the development of vehicle charging infrastructures. Top-level design of tax laws is key to promoting PPP vehicle charging projects. Differential dynamic preferential tax policies favor PPP vehicle charging projects.